CHALLENGES OF DIGITAL TOOLS AND EDUCATION PRACTICES FACED BY TEACHERS IN ONLINE TEACHING DURING THE COVID-19 PANDEMIC - Meirani, Wasitoh; Risnawati; Ardiansyah, Welly; Aryanti, Nurul; Rosyidin, Iskandar; Ujihanti, Murwani (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2022)
ABSTRACT: The spread of COVID-19 has caused widespread disruption of education, forcing schools to seek urgent solutions to reconfigure traditional education programs for distance learning. The emergency restrictions related to social distancing, gathering, etc., have generated a disruption, resulting in a massive quick shift to distance and online teaching. The disruption of teaching has been highly critical and complex, especially for developing countries due to the lack of technological infrastructure, low Internet access, low level of preparation of teachers and parents to use technology, and lack of learning motivation. This paper aimed at identifying the main teaching practices, challenges, and contextual characteristics that have impacted the adoption and use of online teaching solutions during the COVID-19 outbreak. The paper reached this goal by providing the results of a survey involving 25 English teachers taught at senior high schools. The results revealed that despite a set of challenges faced, the online teaching experience during the pandemic time brought improvements in computer teaching skills and communication with students by using several applications for interactivity. Keywords: Challenges and opportunities; online teaching; technology